Spatial updating experiments in Virtual Reality: What makes the world turn around in our head? - Riecke, B. E; Heyde, M. von der; Bülthoff, H. H (5. Tübinger Wahrnehmungskonferenz (TWK), 2002)
During ego-turns, our mental spatial representation of the surround is automatically rotated to stay in alignment with the physical surround. We know that this "spatial updating" process is effortless, automatic, and typically obligatory (i.e., cognitively impenetrable and hard-to-suppress). We were interested in two main questions here: 1) Can visual cues be sufficient to initiate obligatory spatial updating, in contrast to the prevailing opinion that vestibular cues are required? 2) How do vestibular cues, field of view (FOV), display method, turn amplitude and velocity influence spatial updating performance? STIMULI: A photo-realistic virtual replica of the Tübingen market place was presented via a curved projection screen (84x63$^°$ FOV or restricted to 40x30$^°$) or a head-mounted display (HMD, 40x30$^°$). A Stewart motion platform was used for vestibular stimulation. TASK: Participants were rotated successively to different orientations and asked to point "as quickly and accurately as possible" to four targets randomly selected from a set of 22 salient landmarks previously learned. Targets were announced consecutively via headphones and selected to be outside of the visible range (i.e., between 42$^°$ and 105$^°$ left or right from straight ahead). Performance was quantified as absolute pointing error, pointing variability, and response time. In general, participants had no problem mentally updating their orientation in space (UPDATE condition) and spatial updating performance was the same as for rotations where they were immediately returned to the previous orientation (CONTROL condition). Spatial updating was always "obligatory" in the sense that it was significantly more difficult to IGNORE ego-turns (i.e., "point as if not having turned"). We observed this data pattern irrespective of turning velocity, head mounted display (HMD) or projection screen usage, and amount of vestibular cues accompanying the visual turn. Increasing the visual field of view (from 40x30$^°$ FOV to 84x63$^°$) increased UPDATE performance especially for larger turns, i.e., potentially more difficult tasks. IGNORE performance, however, was unaltered. Large turns (>80$^°$) were almost as easy to UPDATE as small turns, but much harder to IGNORE (p<0.05). This suggests that larger turns result in a more obligatory (hard-to-suppress) spatial updating of the world inside our head. We conclude that photo-realistic visual stimuli from well-known environments including an abundance of salient landmarks are sufficient to trigger spatial updating and hence turn the world inside our head, irrespective of vestibular cues. This result conflicts with the prevailing opinion that vestibular cues are required for proper updating of ego-turns. Several factors might explain this difference, primarily the immersiveness of our visualization setup and the abundance of natural landmarks in a well-known environment. SUPPORT: Max Planck Society and Deutsche Forschungsgemeinschaft (SFB 550)
Keywords: Riecke; Riecke_2002; bernhard-riecke; iSpaceWeb; markus-von-der-heyde; spatial updating; talkWithoutPaper